Computing First and Second Fuzzy Zagreb Indices of Linear and Multiacyclic Hydrocarbons. (22nd March 2022) - Mufti, Zeeshan Saleem; Fatima, Eiman; Anjum, Rukhshanda; Tchier, Fairouz; Xin, Qin; Hossain, Md. Moyazzem
Abstract : Fuzzy graph theory was invented by Rosenfeld. It is the extension of the work of L.A. Zadeh on fuzzy sets. Rosenfeld extracted the fuzzy-related concepts using the graph theoretic concepts. Topological indices for crisp theory have already been discussed in the literature but these days, topological index-related fuzzy graphs are much popular. Fuzzy graphs are being used as an application in different fields of sciences such as broadcast, communications, producing, social network, man-made reasoning, data hypothesis, and neural systems. In this paper, we have computed some fuzzy topological indices such as first and second Zagreb indices, Randic index, and harmonic index of fuzzy chemical graph named phenylene.